The Influence of The Family Environment That Results in Children Becoming Crimes - Pasaribu, Yusuf Hanafi (JURNAL AKTA, 2025)
This research aims to analyze legal policies related to the influence of the family environment on the occurrence of criminal acts by children. Children as part of society are often influenced by the environment around them, especially the family, which plays an important role in shaping their character and behavior. In some cases, instability in the family environment can increase the risk of children being involved in criminal activities. Therefore, appropriate legal policies are important in addressing this issue. This study identifies various factors in the family environment that can affect children's behavior, such as family conflict, lack of parental attention, and economic and social factors. In addition, this study also assesses the effectiveness of existing legal policies in dealing with children involved in criminal offenses, including rehabilitation and guidance policies that focus on child recovery rather than punishment alone. The results show that legal policies based on restorative approaches, which prioritize recovery and education for children, have proven to be more effective than repressive punitive policies. It is recommended that legal policies prioritize the role of families in preventing juvenile crime and strengthen coaching programs to help children get back on track. This research also emphasizes the importance of collaboration between legal, educational and social institutions in creating an environment that supports the healthy development of children free from bad influences.